2012
DOI: 10.1371/journal.pone.0029728
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tumor Effect against Human Cancer Xenografts by a Fully Human Monoclonal Antibody to a Variant 8-Epitope of CD44R1 Expressed on Cancer Stem Cells

Abstract: BackgroundCD44 is a major cellular receptor for hyaluronic acids. The stem structure of CD44 encoded by ten normal exons can be enlarged by ten variant exons (v1-v10) by alternative splicing. We have succeeded in preparing MV5 fully human IgM and its class-switched GV5 IgG monoclonal antibody (mAb) recognizing the extracellular domain of a CD44R1 isoform that contains the inserted region coded by variant (v8, v9 and v10) exons and is expressed on the surface of various human epithelial cancer cells.Methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Mazuko and collaborators demonstrated, in vivo, a protective effect of inhibiting the stem cell receptor CD44RI using an antibody against this isoform, in mice previously challenged with 1×10 6 cells from ME180, a human cervical cancer cell line [25]. Furthermore, Feng and collaborators evaluated the presence of CD44 and CK-17 in tumorigenic cervospheres injected into mice challenged with 100,000 total cervosphere cells [26].…”
Section: Discussionmentioning
confidence: 99%
“…Mazuko and collaborators demonstrated, in vivo, a protective effect of inhibiting the stem cell receptor CD44RI using an antibody against this isoform, in mice previously challenged with 1×10 6 cells from ME180, a human cervical cancer cell line [25]. Furthermore, Feng and collaborators evaluated the presence of CD44 and CK-17 in tumorigenic cervospheres injected into mice challenged with 100,000 total cervosphere cells [26].…”
Section: Discussionmentioning
confidence: 99%
“…CD44 has been used for CSC detection and targeting but the mechanism of its involvement in the maintenance of CSCs is not clear. Antibodies against CD44 inhibit breast tumor growth and prevent cancer recurrence [12]. Anti-CD44 antibodies are found to induce the differentiation of acute myeloid leukemia (AML) stem cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…(62) Our recent data provide evidence that the expression of CD44v and its association with an xCT CD98lc block the reactive oxygen species-induced stress signaling that results in growth arrest, cell differentiation and senescence, and, thereby, promote the proliferation of cancer cells and the formation of lethal gastrointestinal tumors, (58) and that anti-CD44v fully human mAb could inhibit tumor formation or tumor growth of xenografted human cancers. (63) Given that CD44v-expressing CSC play a central role in resistance to cancer therapy, it has been suggested that definitive treatment should target the xCT-CD44v high cell population in cancer. (58) We expect that anti-CD98 therapeutic reagents will be applied to various types of human cancers, and that CD98hc/CD98lc Fig.…”
Section: Discussionmentioning
confidence: 99%